2023
DOI: 10.1021/acs.jafc.3c01782
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase UvHST2 Is a Global Regulator of Secondary Metabolism in Ustilaginoidea virens

Ling Liu,
Bo Wang,
Guohua Duan
et al.

Abstract: Ustilaginoidea virens, the causal agent of rice false smut, produces a large amount of mycotoxins, including ustilaginoidins and sorbicillinoids. However, little is known about the regulatory mechanism of mycotoxin biosynthesis inU. virens.Here, we demonstrate that the NAD + -dependent histone deacetylase UvHST2 negatively regulates ustilaginoidin biosynthesis. UvHst2 knockout caused retarded hypha growth and reduced conidiation and pathogenicity inU. virens. Transcriptome analysis revealed that the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The culture of U. virens generates multiple types of mycotoxins, such as ustilaginoidins and sorbicillinoids (Liu, Wang, et al., 2023 ; Zhang, Xu, et al., 2022 ). The mycotoxin biosynthesis‐related genes in DEGs are summarized in Table S7 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The culture of U. virens generates multiple types of mycotoxins, such as ustilaginoidins and sorbicillinoids (Liu, Wang, et al., 2023 ; Zhang, Xu, et al., 2022 ). The mycotoxin biosynthesis‐related genes in DEGs are summarized in Table S7 .…”
Section: Resultsmentioning
confidence: 99%
“…Ustilaginoidins, one of the major types of mycotoxins in U. virens , are toxic to humans and livestock and threaten food safety. Although HDACs have been reported to be key players in regulating gene expression and secondary metabolism in fungi, knowledge about HDAC functions in virulence and mycotoxin biosynthesis in U. virens is scarce (Liu, Wang, et al., 2023 ). In this study, we not only demonstrated that a class II HDAC UvHOS3 positively regulates vegetative growth and development, conidiation and pathogenicity, but also revealed that UvHOS3 inhibits biosynthesis of mycotoxins, especially ustilaginoidins and sorbicillinoids in U. virens .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations